Mulheres que “Botam banca”: Um estudo antropológico sobre trabalho, família e vizinhança, a partir da atividade de venda de comida em bairros populares de Santarém/PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
In Santarem we can observe various food stalls offering traditional food , barbecue and snacks. These spaces are also seen as local networks of social relations and symbolic exchanges that pass their own monetary relations and thus shifting the focus from purely economic issues, arising thoughts about work , neighborhood, family. The methodology used were questionnaires and interviews with 22 women who put food stalls, as well as participant observation and informal conversations. Thus it was realized that the occupation played by them is usually learned in childhood , so that the interviews reveal that women starts "helping” at home and in the fields for around 10 years old. After establishing marital relationships these women opt for development activities that enable more easily to reconcile paid work and family care .
Keywords: Economia; Família; Gênero; Vizinhança; Santarém; CNPQ:: CIÊNCIAS HUMANAS